Timing of operation in children with a prenatal diagnosis of choledochal cyst: A single‐center retrospective study. (10th May 2022) - Guan, Xisi; Li, Junting; Wang, Zhe; Zeng, Jixiao; Zhong, Wei; Yu, Jiakang
Abstract: Background/Purpose: There is currently no consensus on the timing of operative correction for patients with a prenatal diagnosis of choledochal cyst (CDC). This study aims to retrospectively analyze patients with prenatally diagnosed CDCs to identify the optimal timing of operative correction and the importance of cyst size as a predictor of the appearance of symptoms related to the CDC. Methods: We reviewed 125 patients with a prenatal diagnosis of CDC who were admitted to Guangzhou Women and Children's Medical Center from July 2015 to July 2020. After dividing the patients into a symptomatic group (n = 37) and an asymptomatic group (n = 88), according to whether they had any clinical symptoms at the time of their operation, we compared their clinical data and postoperative outcomes. The asymptomatic group was divided into a <1 month group; a ≥1 month and <4 months group; and a ≥4 months group according to their postnatal age at operation; postoperative complications of the three groups were then compared. We were also interested in the effect of cyst size (width and length) for predicting the development of symptoms related to the CDC. Results: The time of onset of symptoms after birth was mainly concentrated in the first 3 months (48.6%). The median width and length of cysts measured by preoperative magnetic resonance cholangiopancreatography in the symptomatic group were greater than those in the asymptomatic group (43 mm vs 28 mm and 71 mm vs 45 mm, respectively; P < .05). The serum levels of the liver‐related enzymes ALT, AST, and GGT, and the serum level of DBIL, were greater in the symptomatic group than in the asymptomatic group ( P < .05). The operative time, intraoperative blood loss, and duration of postoperative hospital stay in the symptomatic group were greater than those in the asymptomatic group ( P < .05). In the asymptomatic group, there were no statistically significant differences in the surgical data and postoperative complications between the <1 month group, the ≥1 month and <4 months group, and the ≥4 months group. The area under the receiver operating characteristic curve (AUROC) of the length of the cyst in predicting symptoms was 0.747, the best cut‐off point was 5.2 cm, and the sensitivity and specificity were 78% and 70%, respectively. The AUROC of the width of the cyst was 0.704, the best cut‐off point was 4.1 cm, and the sensitivity and specificity were 68% and 75%, respectively. Conclusion: We maintain that it is advantageous to receive surgical treatment in the asymptomatic period for patients with a prenatally diagnosed CDC. A cyst size of length >5.2 cm and width >4.1 cm suggested that clinical symptoms might appear, and that surgery should be carried out as soon as possible, even in the neonatal period.